Can South Africa / Nigeria relations be recalibrated? - Gopaldas, Ronak (2020)
South Africa and Nigeria, the two African powerhouses, experience a rocky relationship. The leadership of the time tends to set the tone. Sani Abacha and Nelson Mandela clashed over human rights abuses. Mbeki and Obasanjo developed close ties and shared their vision of a united continent. A return to tumult under Zuma and Jonathan reversed this positive trend. Following the xenophobic outbreak of violence in South Africa, the two countries must now reconcile forceful responses from all quarters. These events bring their often-volatile relationship into sharp focus. However, the episode may emerge as a catalyst for resetting bilateral ties across political, social and business domains. Both Presidents Cyril Ramaphosa and Muhammadu Buhari see enormous upside potential from building a far closer working relationship. Healing rifts between the continent’s two biggest (and slowest growing) economies has never been more important. Overcoming the critical barriers to the social and economic advancement of Africa will require putting egos, ideological differences, short-termism, and competitive rivalries aside. This article explores the tensions between the two countries and the potential that recent events will lead to a pact that benefits not only the two countries, but also the continent as a whole. It will examine how a changing approach to diplomacy may foster more stable relations, unpack the economic rivalry between the countries, review how mistrust and political overreach strained commercial relations, and explore the impacts on businesses.